Intratumoral H2O2-triggered release of CO from a metal carbonyl-based nanomedicine for efficient CO therapy. Issue 40 (5th May 2017) - Jin, Zhaokui; Wen, Yanyuan; Xiong, Liwei; Yang, Tian; Zhao, Penghe; Tan, Liwei; Wang, Tianfu; Qian, Zhiyong; Su, Bao-Lian; He, Qianjun
Abstract : H2 O2 -triggered release of CO: an intratumoral H2 O2 -responsive nanomedicine is constructed by effectively encapsulating the hydrophilic manganese carbonyl prodrug into an advanced hollow mesoporous silica nanoparticle carrier to realize selective killing of tumor cells, exhibiting high in vitro and in vivo efficacies of CO gas therapy. Abstract : A new H2 O2 -responsive nanomedicine for CO therapy is constructed by effectively encapsulating the hydrophobic manganese carbonyl prodrug into an advanced hollow mesoporous silica nanoparticle carrier to realize the intratumoral H2 O2 -triggered release of CO and selective killing of tumour cells rather than normal cells, exhibiting high in vitro and in vivo efficacies of CO therapy.